2007
DOI: 10.2308/jis.2007.21.1.53
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of User Characteristics on Query Performance in the Presence of Information Request Ambiguity

Abstract: 5This paper investigates the effects of personality characteristics on individuals' abilities to 6 compose queries from information requests containing various types of ambiguity. In particular, 7 this research examines the effects of user personality characteristics on query performance in the 8 presence of information requests that contained no, extraneous, syntactic, or both extraneous and 9 syntactic ambiguities. The results indicate that personality characteristics significantly affect 10 users' abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
2
1
Order By: Relevance
“…As per results, hypothesis four had no substantial effect on willingness to adopt solar PV. This result differed from previous research findings, which showed that customers with a high degree of openness were enthusiastic about emerging technology, and their acceptability was high [128,129]. Previous studies conducted in developed countries show that the adoption of new emerging technologies is common there.…”
Section: Openness To Technology and Willingness To Adopt Solar Pvcontrasting
confidence: 97%
“…As per results, hypothesis four had no substantial effect on willingness to adopt solar PV. This result differed from previous research findings, which showed that customers with a high degree of openness were enthusiastic about emerging technology, and their acceptability was high [128,129]. Previous studies conducted in developed countries show that the adoption of new emerging technologies is common there.…”
Section: Openness To Technology and Willingness To Adopt Solar Pvcontrasting
confidence: 97%
“…This finding is consistent with findings of previous research (Ashkanasy et al 2007;Korukonda 2007;Li et al 2006). The study data indicate that the executives who score high on openness tend to display a proclivity to not only listen to new ideas, but also to change their own ideas and beliefs and consequently change their behavior as a result of new experiences and information.…”
Section: Supportedsupporting
confidence: 94%
“…The effect of openness on people's interaction with technology has been an increasing focus of studies in recent years (e.g. Ashkanasy et al 2007), with a variety of findings, including a positive association between openness and job satisfaction in an environment of continuing technological change (Gallivan 2004) and a negative association between openness and technophobia (Anthony et al 2000). Li et al (2006) demonstrated that the personality traits of openness to experience among chief information officers have a positive impact on their firms' innovative usage of IT.…”
Section: Opennessmentioning
confidence: 99%
“…4f). Perhaps there was a growing trend that students communicate with each other more and more, perhaps students are more and more skilled in utilizing internet search engines, or perhaps students have more and more certain personal characteristics -a factor which has been studied to affect query writing performance (Ashkanasy et al, 2007). Additionally, and although we used the same teaching materials for each cohort, it is possible, even likely, that the teacher's skills develop over time (Fig.…”
Section: Differencesmentioning
confidence: 99%